Financial Intermediary Development, Output And Export Under Credit Market Imperfections - Tang, Kin Boon (2007)

(untitled)
This study examines the long-run relationship between financial intermediary development, output and export under three credit market imperfections – role of financial intermediaries, financial accelerator and currency mismatch. In particular, this study has (1) examined the direct relationship between financial intermediary development and output fluctuations (2) examined the dampening and magnifying effects of financial intermediaries on output fluctuations via the propagation of real and monetary shocks, (3) examined the impact of exchange rate movements on exports under the condition of foreign currency borrowing and credit constraint and (4) evaluated the impact of external finance premium on various sectorial productions and aggregate outputs growth. An aggregate data panel is constructed for the countries under study and the cointegration hypothesis among the variables is verified using Pedroni’s and Westerlund’s panel cointegration tests. The idiosyncratic, individual and group-mean panel cointegrating vectors are then estimated using FMOLS and DOLS developed by Pedroni.Using data from 17 countries at different income levels in East Asia-Pacific, the empirical results indicate that (1) strong and robust evidence for dampening effect of real shocks, (2) somewhat weak evidence for magnifying effect of monetary shocks, (3) financial intermediary development to some extent have direct impact on output fluctuations if countries are bank-dependent, (4) the larger the level of country’s foreign debt and credit constraint results more negative response of exports to currency depreciation, (5) country’s export with high foreign currency denominated debt are more vulnerable to negative exchange rate shocks and (6) the negative relationship between the external finance premium and the aggregate output growth seems to be strengthened in middle income than in the sectorial production growth.